El poder formativo de la democracia como sinónimo de democracia plena. Educación en la democracia y vida en colectivo (2011)
ABSTRACT: Formative power of democracy as a synonym for full democracy. Education in democracy and collective life, Andrés López Bermúdez. Are discussed here two conflicting views about the nature of democracy, seeking to understand the obstacles, contradictions and challenges facing today. As Norberto Bobbio as democracy takes on its true nature through the procedures with which expresses, Cornelius Castoriadis argues that its essence lies beyond, which must be seen as a phenomenon that emanates from the character and training of citizens that aspire as the best form of government. To them, according to Castoriadis, as subjects engaged in a lifelong learning process, it is always unfinished task-democracy-building, rather than, as claimed by Bobbio, institutions and laws.